“Parallels”: Social justice through artmaking and the archives - Prasad, Sheetal (YU-WRITE: Journal of Graduate Student Research in Education, 2022)
Inspired by Thai artist Manit Sriwanichpoom (1997-2008), I created a series of photographic prints in 2019 called Sheila and the… (Figures 1-3) depicting in the foreground (in colour) my alter ego named “Sheila” against a black and white background of a historical event. Using a similar format, Parallels: Sheetal and the… (2022) (Figures 4-6) speaks to the shift that many have witnessed since the start of the Covid-19 pandemic. Both series address the ongoing cycles of historical events and colonial violence. I posit that by engaging in history through artmaking, students can better understand the cycles of colonial narratives and navigate social justice issues in our lived experiences.